Issues occupying our minds: Nomenclature of autoimmune blistering diseases requires updating, pemphigus vulgaris propensity to affect areas adjacent to natural body orifices unifies seemingly diverse clinical features of this disease - Dmochowski, Marian; Jałowska, Magdalena; Bowszyc-Dmochowska, Monika (Frontiers in Immunology, 2022)
In this conceptual analysis, we present our concepts on two issues regarding autoimmune bullous diseases (AIBD), namely (i) current nomenclature of AIBD requires updating by incorporating molecular data and (ii) pemphigus vulgaris (PV) “likes” areas adjacent to natural body orifices. The problem of inadequacy of the currently used nomenclature was noticed recently by Zillikens, who proposed to form a group with the task of updating it. The early efforts by Dmochowski to update this nomenclature happened to be a daunting task. Nevertheless, the ideal nomenclature should retain the bulk of clinical data, which generations of dermatologists are accustomed to, including triggers if known, and incorporate molecular data revealing targets of autoimmune response and immunoglobulin isotypes involved. The natural body orifices affected by PV were previously described in numerous publications. However, these openings are described separately in these publications. Here, Dmochowski comes up with an intellectual concept that this propensity of PV unifies seemingly diverse clinical features of this disease.